Experimental study of electrical discharge drilling of stainless steel UNS S30400 - Hanash, Ebrahim; Ali, Mohammad Yeakub (Institute of Physics Publishing, 2018)
In this study, overcut and taper angle were investigated in machining of stainless steel UNS S30400 against three different electrical discharge machining parameters which are electric current (Ip), pulse on-time (Ton) and pulse off-time (Toff). The electrode used was of 1 mm diameter with aspect ratio of 10. Dimensional accuracy was measured by evaluating overcut and taper angle. Those two measurements were performed using optical microscope model (Olympus BX41M, Japan). The experimentation planning, evaluation, analysis and optimization have been carried out using DOE software version 10.0.3 RSM based method with total number of twenty experiments. The research reveals that, discharge current was found to have the most significant effect on overcut and taper angle followed by pulse on-time and pulse off-time. As the discharge current and pulse on-time increase, overcut and taper angle are increased. However, when pulse off-time increases, overcut and taper angle decrease. The outcome result of this study will be very useful in the manufacturing industry to select the appropriate parameters for the selected work material. The model has shown a great accuracy with percentage error of less than 5%.